2018
DOI: 10.1542/hpeds.2017-0194
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of Routine HIV Testing by Hospitalized Adolescents and Young Adults

Abstract: Our findings support offering routine HIV testing to youth admitted to children's hospital. Given the high incidence of new and undiagnosed HIV infections among youth, additional venues for HIV testing are essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(37 reference statements)
1
5
0
Order By: Relevance
“…The 59 studies encompassed male and female adolescents and young adults from 5 continents (North America, Africa, Asia, Australia, and Europe), with the majority of studies (n=39) taking place in North America 11-55. Reported utilization of model of care differed by continent, with the most common model of care in North America being the ED (n=17), followed by community settings (n=11).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 59 studies encompassed male and female adolescents and young adults from 5 continents (North America, Africa, Asia, Australia, and Europe), with the majority of studies (n=39) taking place in North America 11-55. Reported utilization of model of care differed by continent, with the most common model of care in North America being the ED (n=17), followed by community settings (n=11).…”
Section: Resultsmentioning
confidence: 99%
“…Studies were included if the participants were adolescents (ages [13][14][15][16][17] or young adults (ages 18-24) who were offered HIV testing. Participants who were pregnant or acquired HIV via vertical (mother to infant) transmission were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical students have more opportunities to receive medical-related information, thereby developing stronger awareness of HIV prevention and treatment. In terms of personal views, sexual behavior and sexual education were influencing factors of the acceptance for detection in college students [ 52 , 57 ]. Those students have more demand for HIV testing, hence HIV screening on college campus is essential.…”
Section: Discussionmentioning
confidence: 99%
“…However, if it is not done in the ED, the wards are another opportunity to provide these services. In "Acceptance of Routine HIV Testing by Hospitalized Adolescents and Young Adults," Bhalakia et al 18 explored how routine HIV testing on admission to an urban, academic, pediatric hospital was received by patients aged 13 to 24 years. The authors found that approximately one-half of the patients (47%) accepted HIV testing.…”
mentioning
confidence: 99%